2014
DOI: 10.1175/wcas-d-13-00021.1
|View full text |Cite
|
Sign up to set email alerts
|

Tornado Warning Trade-Offs: Evaluating Choices for Visually Communicating Risk

Abstract: Recent improvements in weather observation and monitoring have increased the precision of tornado warnings. The National Weather Service currently issues storm-based tornado warnings, and even more geographically specific warnings that include probability information are under development. At the same time, the widespread proliferation of smartphone and mobile computing technology supports the rapid dissemination of graphical weather warning information. Some broadcasters and private companies have already beg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
96
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 49 publications
15
96
0
1
Order By: Relevance
“…The amount of uncertainty inferred was equal between the fan plot and worded probability at 50%. This result suggests that, similar to previous literature with more familiar natural‐hazard forecasts (e.g., tornado, temperature, hurricane; Ash et al ., ; Ruginski et al ., ; Tak et al ., ), interpretations of forecast information can be different when given different forecast representations for an unfamiliar hazard. Interpreting uncertainty differently depending on differing forecast representations could be problematic in real‐life decision‐making situations; for example, increasing coastal protection as an adaption to sea‐level rise.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of uncertainty inferred was equal between the fan plot and worded probability at 50%. This result suggests that, similar to previous literature with more familiar natural‐hazard forecasts (e.g., tornado, temperature, hurricane; Ash et al ., ; Ruginski et al ., ; Tak et al ., ), interpretations of forecast information can be different when given different forecast representations for an unfamiliar hazard. Interpreting uncertainty differently depending on differing forecast representations could be problematic in real‐life decision‐making situations; for example, increasing coastal protection as an adaption to sea‐level rise.…”
Section: Discussionmentioning
confidence: 99%
“…The findings from two lab-based studies by Wu et al [37,38] support the finding that people tend to focus on the forecast track, gleaning little information from the rest of the graphic. Other challenges with maps include confusion between probability maps and scenario maps [39] and misjudgment of risk when polygons are used to show risk zones [40,41]. Although people at least sometimes are able to infer that the edge of a polygon does not indicate a divide between an area at risk and an area completely not at risk [38,41], there is some evidence that people infer a higher risk at the center of the polygon [41].…”
Section: Objective Versus Subjective Probability Estimatesmentioning
confidence: 99%
“…For example, researchers have found that visual design of wildfire hazard maps can influence people's interest and engagement with the hazard information and also how they use it to make decisions about evacuation (Cao et al 2016;Cheong et al 2016). Similarly, visual design has been found to influence emotional and behavioural responses to tornado warning maps (Ash et al 2014). Visualising and communicating uncertainty in geospatial data also remains an ongoing challenge across many different fields (Aerts et al 2003;Spiegelhalter et al 2011;Kinkeldey et al 2014).…”
Section: Exploring and Testing Different Designsmentioning
confidence: 99%